Novel nano material and immobilized enzyme and application thereof
By preparing spherical mesoporous nanomaterials and synthesizing immobilized enzymes in combination with bionic mineralization, the problems of restricted enzyme catalysis and insufficient selectivity of immobilized enzymes in the prior art are solved, the efficient catalysis and stability of the enzyme are achieved, and the scope of application in industrial applications is broadened.
Patent Information
- Application Number
- CN202411861883.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Prior Art When immobilizing enzymes, the microporous structure of the metal polynizole framework limits the diffusion of large-sized substrates, resulting in limited enzyme catalysis. At the same time, the limited selection of MOF types of immobilized enzymes, hindering its widespread use in industrial applications.
By changing the order of addition of substances in the system, spherical mesoporous nanomaterials were prepared, and immobilized enzymes were synthesized in combination with bionic mineralization to form nanomaterials with excellent biocompatibility and stability. The mesoporous structure of this nanomaterial promotes the contact between substrate and enzymes, improves the catalytic activity of enzymes, and protects the enzymes under harsh conditions such as high temperatures, acid and alkali.
The efficient catalytic reaction of enzymes is achieved, the enzyme recycling ability and storage ability are improved, the activity of immobilized enzymes is increased by more than twice, suitable for most enzymes, and the application scope of the strategy of immobilizing enzymes in metal-organic frameworks is broadened.
Smart Images

Figure CN119661866A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the fields of biology, materials, water environment management and environmental protection technology, and in particular to a novel nanomaterial and an immobilized enzyme and application thereof. Background Art
[0002] In recent years, with the increasing eutrophication of water bodies and global warming, the frequency and scope of harmful microcystis blooms (HMBs) have gradually increased. The stench of water bodies caused by HMBs seriously affects the normal life of local residents. In addition, the MCs released by Microcystis into the water bodies will poison aquatic plants and animals. The median lethal dose (LD50) of MC-LR (a type of MCs) to mice is about 50-100 μg / kg. When people bathe, swim, or engage in other water leisure and sports, skin contact with water containing MCs can cause allergies in sensitive parts (such as eyes) and skin; a small amount of intake can cause acute gastroenteritis; long-term drinking may cause liver cancer.
[0003] The algal toxin degrading enzyme (MlrA) can efficiently degrade algal toxins while inhibiting the growth of Microcystis (Liu et al., Environ. Sci. Techol., 2020, 54, 8811-8820). As a product of nature, MlrA achieves high catalytic efficiency in cells, but under actual water conditions that are very different from the cellular environment, the lifespan and efficiency of the enzyme tend to decrease, which poses a challenge to the application of the enzyme. One way to address these challenges is to guide the evolution of enzymes by changing the molecular structure of proteins. Another way is to design a bionic microenvironment to protect enzymes so that their functions can be maintained in adverse environments.
[0004] Metal-organic frameworks (MOFs) are spatial topological structures formed by metal ions and organic linkers, with porous structures and balanced rigidity and flexibility, similar to the cellular environment. Pioneering work has shown that encapsulating enzymes in MOFs can achieve better functions under general conditions. Among them, new methods, such as biomimetic mineralization, simply mix enzymes, metal ions and organic ligands in bulk solutions under ambient conditions to prepare composite materials of MOF-encapsulated enzymes. This method is an efficient, direct and scalable method for preparing MOF biocomposites, which can protect enzymes and other fragile biomolecules. The hydrophobic metal imidazole framework (ZIF-8) in MOF cannot provide effective protection, while the hydrophilic metal polynitrogen framework (MAF-7) has potential application potential (Liu et al., J.Am.Chem.Soc., 2019, 141, 2348-2355).
[0005] However, the biomimetic mineralization method has great limitations. Since the metal polyazole framework is generally reported to be a microporous structure, it severely restricts the diffusion of large-sized substrates, resulting in limited enzyme catalysis. In addition, the types of MOFs that can be selected for enzyme immobilization based on the biomimetic mineralization method are limited, which greatly hinders the application of this strategy in industry. Summary of the invention
[0006] In order to overcome the problems existing in the prior art, the present application provides a new type of nanomaterial and its immobilized enzyme and application. The nanomaterial has excellent biocompatibility and mild synthesis conditions. At the same time, it can protect the enzyme from reacting under harsh conditions such as high temperature, acid and alkali, and increase the circulation and storage capacity of the enzyme.
[0007] In order to solve the above technical problems, the technical solution adopted in this application is:
[0008] In the first aspect, the present application provides a new type of nanomaterial, which is a spherical mesoporous nanomaterial with a particle size of 2 to 30 μm and a surface pore size of 2 to 30 nm; the new type of nanomaterial is prepared by the following method: an alkaline solution is added to a metal salt solution and mixed thoroughly, and then a ligand aqueous solution is added, and the solid product is separated after sufficient mixing.
[0009] In a second aspect, the present application provides an immobilized enzyme obtained by immobilizing an enzyme on a novel nanomaterial, wherein the particle size of the immobilized enzyme is 2 to 20 μm and the pore size on the surface is 1 to 15 nm. The immobilized enzyme is prepared by the following method: mixing the enzyme with an aqueous solution of a ligand, then adding the mixture to a mixed solution of a metal salt solution, and separating the solid product.
[0010] In a third aspect, the present application provides the use of novel nanomaterials and immobilized enzymes in inhibiting the growth of cyanobacteria and / or degrading algal toxins, wherein the cyanobacteria are selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc, and Pseudo-Anabaena; and the algal toxins are selected from at least one of MC-LR, MC-YR, MC-RR, and Nodularin.
[0011] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0012] The present application changes the order of adding substances in the system to produce a mesoporous structure of nanomaterials, and synthesizes immobilized enzymes by a biomimetic mineralization method, which is simple to operate, low in price and high in efficiency. The mesoporous structure of nanomaterials is conducive to the contact between substrate and enzyme, prompting the enzyme to perform efficient catalytic reactions, and can protect the enzyme from the influence of environments such as high temperature and acid-base solutions, and increase the recycling and storage capacity of the enzyme. More importantly, immobilized enzymes allow large-sized substrates to enter the shell of nanomaterials, so this method is applicable to most enzymes.
[0013] The present application obtains a new type of nanomaterial and its immobilized enzyme by a biomimetic mineralization method. Compared with non-porous nanomaterials of the same type and typical similar materials ZIF-8, the activity of the immobilized enzyme obtained by the new type of nanomaterial obtained by the present application after the enzyme is immobilized is more than doubled. After the enzyme is immobilized, the new type of nanomaterial has the effect of synergistically inhibiting the growth of toxic cyanobacteria, and has excellent enzyme catalytic ability, reaction stability, recycling ability and storage capacity, thereby greatly broadening the application scope of the strategy of fixing enzymes on metal organic frameworks. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 is the X-ray powder diffraction pattern of the nanomaterial and the immobilized enzyme in Example 1;
[0016] Figure 2 is a scanning electron microscope image of the nanomaterial and the immobilized enzyme in Example 1;
[0017] Figure 3 The degradation effect of the nanomaterial-immobilized algae toxin degrading enzyme A on MCs (MC-LR, MC-RR, MC-YR) in Example 2;
[0018] Figure 4 This is a diagram showing the inhibitory effect of nanomaterial-immobilized algae toxin degrading enzyme A on Microcystis aeruginosa FACHB-905 in Example 6. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.
[0021] A new type of nano material, the nano material is spherical mesoporous, the particle size is 2 to 30 μm, and the surface pore size is 2 to 30 nm; the new type of nano material is prepared by the following method: adding an alkaline solution to a metal salt solution and fully mixing it, then adding a ligand aqueous solution, separating the solid product after sufficient reaction to obtain the nano material.
[0022] In some embodiments of the present application, the concentration of the alkaline solution is 0.25-0.75% (w / w); the concentration of the metal salt aqueous solution is 20-400 mM, and the metal salt solution is a zinc salt solution.
[0023] In some embodiments of the present application, the zinc salt is at least one of zinc nitrate, zinc acetate, zinc chloride and zinc sulfate.
[0024] In some embodiments of the present application, the ligand is 3-methyl-1,2,4-1H-triazole and its derivatives, the concentration of the ligand aqueous solution is 120-1200 mM, and the molar ratio of the metal salt to the ligand is 1:(3-5).
[0025] In some embodiments of the present application, the solid product is separated by centrifugation, specifically centrifugation at a speed of 6000-12000 rpm for 2-10 min, and finally the separated solid product is washed twice with secondary water.
[0026] The invention discloses an immobilized enzyme of a novel nano material. The particle size of the immobilized enzyme is 2-20 μm, and the pore size on the surface is 1-15 nm.
[0027] In some embodiments of the present application, the immobilized enzyme is prepared by the following method: the enzyme is mixed with an aqueous ligand solution, and then added to a mixture of a metal salt solution and an alkaline solution, wherein the final concentration of the enzyme in the mixture is 0.5 mg / mL, and the immobilized enzyme is obtained by separating the solid product.
[0028] In some embodiments of the present application, the concentration of the alkaline solution is 0.25-0.75% (w / w); the concentration of the metal salt aqueous solution is 20-400mM, the metal salt solution is zinc salt, copper salt, cobalt salt, nickel salt solution, and the metal salt is at least one of nitrate, acetate, chloride and sulfate; the ligand is 3-methyl-1,2,4-1H-triazole and its derivatives, and the concentration of the ligand aqueous solution is 60-1200mM; the molar ratio of metal salt to ligand is 1: (3-5). The above-mentioned solid product is separated by centrifugation, and the centrifugation is specifically centrifuged at a speed of 6000-12000rpm for 2-10min, and the separated solid product is finally washed twice with secondary water.
[0029] A novel nanomaterial is used for inhibiting the growth of cyanobacteria and / or degrading algal toxins. The cyanobacteria are selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc and Pseudo-Anabaena; and the algal toxins are selected from at least one of MC-LR, MC-YR, MC-RR and Nodularin.
[0030] The invention discloses an application of a novel nanomaterial-immobilized enzyme in inhibiting the growth of cyanobacteria and / or degrading algal toxins. The cyanobacteria are selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc and Pseudo-Anabaena; and the algal toxins are selected from at least one of MC-LR, MC-YR, MC-RR and Nodularin.
[0031] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0032] Example 1
[0033] This example screens and optimizes the conditions for preparing a new type of nanomaterial and its immobilized enzyme.
[0034] The novel nanomaterial (DMOF) and its immobilized algae toxin degrading enzyme (MlrA@DMOF) were prepared in the following steps:
[0035] Weigh 0.4750 g of zinc nitrate hexahydrate into a 5 mL EP tube and add 4 mL of secondary water to dissolve;
[0036] Weigh 0.0665 g, 0.1000 g, 0.1329 g, and 0.1662 g of 3-methyl-1H-1,2,4-triazole (Hmtz) respectively into a 5 mL EP tube and add 1 mL of secondary water to dissolve them to obtain Hmtz solutions 1, 2, 3, and 4;
[0037] 100 μL of Hmtz solution and 780 μL of secondary water were transferred to a 1 mL EP tube, and a mixed solution of 100 μL of zinc nitrate solution and 20 μL of ammonia water (12.5%) was added, and the mixture was shaken for 30 min. The obtained solid was centrifuged at 8000 rpm for 10 min and washed twice with secondary water to obtain spherical mesoporous nanomaterial samples, which were marked as nanomaterial sample 1, sample 2, sample 3, and sample 4, respectively.
[0038] 100 μL Hmtz solution and 580 μL secondary water were transferred to a 1 mL EP tube, and 100 μL Tris buffer (25 mM) and 100 μL 5 mg / mL MlrA solution were added. Then, a mixed solution of 100 μL zinc nitrate solution and 20 μL ammonia water (12.5%) was added, and the mixture was shaken for 10 min and allowed to stand for 20 min. The obtained solid was centrifuged at 8000 rpm for 10 min, washed twice with secondary water, and resuspended in 200 μL Tris (25 mM) to obtain the immobilized enzyme solution, which were immobilized enzyme (MlrA@DMOF) samples 1, 2, 3, and 4, respectively.
[0039] 10 μL of 40 μg / mL MC-LR was added to 381 μL of 50 mM phosphate buffer solution (pH = 7), and 4 experimental groups were set up and parallel groups were set up. 5 μL of 0.5 mg / mL MlrA@DMOF samples 1, 2, 3, and 4 were added to the above different experimental group solutions, reacted at room temperature for 5 minutes, and finally 4 μL of 20% phosphoric acid aqueous solution was added to terminate the reaction.
[0040] After the reaction, the residual MC-LR and its products in the supernatant were detected by high performance liquid chromatography (HPLC) to determine the activity of the immobilized enzyme, the protein content in the supernatant was determined to determine the immobilization rate of the immobilized enzyme, and the sample morphology was observed by scanning electron microscopy. The results are shown in Table 1. Sample 1 did not form a regular microscopic morphology, indicating that a certain concentration of 3-methyl-1H-1,2,4-triazole (Hmtz) was required to better form regular nanomaterials. The activity of the immobilized enzyme decreased with the increase of the Hmtz concentration. Therefore, the synthesis conditions of sample 2 are suitable conditions for the synthesis of nanomaterials and immobilized enzymes.
[0041] Table 1 Morphology, immobilization rate and activity of nanomaterials and immobilized enzymes
[0042]
[0043] The nanomaterial and immobilized enzyme of sample 2 of this embodiment were subjected to X-ray powder diffraction analysis. Figure 1 As shown. Figure 1 It can be seen that the characteristic peaks of the nanomaterials are consistent with those of the standard samples, proving the successful synthesis of DMOF. The characteristic peaks of the immobilized enzyme have not changed significantly, proving that the crystal structure of DMOF has not changed significantly after encapsulating the enzyme.
[0044] The nanomaterial and immobilized enzyme of sample 2 of this embodiment were scanned by electron microscope. Figure 2 As shown, Figure 2a, b are nanomaterials; c, d are immobilized enzymes; Figure 2 It can be seen that both the nanomaterials and the immobilized enzymes are durian-like spheres, and some fine particles are added to the surface of the immobilized enzymes, which may be enzyme aggregates.
[0045] Example 2
[0046] This example verifies the good catalytic ability of the immobilized enzyme.
[0047] The activity of the immobilized algae toxin degrading enzyme (MlrA@DMOF) prepared in Example 1 was compared with that of the free enzyme. The steps are as follows:
[0048] (1) Take 10 μL of 40 μg / mL MC-LR, MC-YR and MC-RR and add them into 381 μL 50 mM phosphate buffer solution (pH=7), set samples as 1, 2, 3 and set parallel groups.
[0049] (2) 5 μL of 0.5 mg / mL MlrA@DMOF was added to the above samples 1, 2, and 3 and reacted at room temperature for 5 minutes. Two groups were set up in parallel, and finally 4 μL of 20% phosphoric acid aqueous solution was added to terminate the reaction. After centrifugation at 12000 rpm for 1 hour, the residual MC-LR in the supernatant was detected by HPLC.
[0050] The MlrA activity was carried out according to the same steps as (1) and (2) above, except that MlrA was used instead of MlrA@DMOF.
[0051] The results are as follows Figure 3 As shown, from Figure 3 It can be seen that MlrA@DMOF retains the catalytic activity of MlrA and has good degradation activity for three common algal toxins (MC-LR, MC-YR, and MC-RR).
[0052] Example 3
[0053] This example verifies the good temperature stability of MlrA@DMOF.
[0054] MlrA@DMOF has good temperature and pH stability, and the reaction activity of MlrA@DMOF and MlrA was compared. The steps are:
[0055] (1) Take 10 μL of 10 μg / mL MC-LR and add it into 9 EP tubes containing 381 μL of 50 mM sodium phosphate buffer solution (pH=7). Samples are 1, 2, 3, 4, 5, 6, 7, 8, and 9.
[0056] (2) After incubating MlrA@DMOF at a concentration of 0.5 mg / mL at 30°C, 35°C, 40°C, 45°C, 50°C, and 60°C for 1 h, 5 μL was added to samples 1, 2, 3, 4, 5, 6, 7, 8, and 9, and reacted at 25°C for 5 minutes. After that, 4 μL of 20% phosphoric acid aqueous solution was added to terminate the reaction. After centrifugation at 12000 rpm for 1 h, the residual MC-LR in the supernatant was detected by HPLC.
[0057] (3) MlrA activity test control The same steps as above (1) and (2) were followed, except that MlrA was used instead of MlrA@DMOF.
[0058] The results are shown in Table 2.
[0059] Table 2 Residual activity of MlrA@DMOF and MlrA after incubation at different temperatures for 1 h
[0060]
[0061] As can be seen from Table 2, after incubation at 30-50 °C for 1 h, MlrA@DMOF retained more activity than MlrA, proving that MlrA@DMOF has stronger thermal stability.
[0062] Example 4
[0063] This example verifies the good pH stability of MlrA@DMOF.
[0064] (1) Take 10 μL of 10 μg / mL MC-LR and add it into 11 EP tubes containing 381 μL of 50 mM sodium phosphate buffer solution (pH=7), and mark the samples as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11 respectively.
[0065] (2) After incubating the MlrA@DMOF with a concentration of 0.5 mg / mL in a buffer solution of pH = 3, 4, 5, 6, 6.5, 7, 7.5, 8, 9, 10, 11 for 1 h, 5 μL was added to samples 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 respectively, reacted at 25°C for 5 minutes, and then 4 μL of 20% phosphoric acid aqueous solution was added thereto to terminate the reaction. After centrifugation at 12000 rpm for 1 h, the residual MC-LR in the supernatant was detected by HPLC.
[0066] (3) MlrA activity test control The same steps as above (1) and (2) were followed, except that MlrA was used instead of MlrA@DMOF.
[0067] The results are shown in Table 3.
[0068] Table 2 Residual activity of MlrA@DMOF and MlrA after incubation for 1 h at different pH values
[0069]
[0070] As can be seen from Table 3, after incubation for 1 h at pH 3-8, MlrA@DMOF retained more activity than MlrA, proving that MlrA@DMOF has stronger acid resistance.
[0071] Example 5
[0072] This experiment verifies the good storage stability of MlrA@DMOF and compares the activity of MlrA@DMOF with that of free enzyme MlrA. The steps are as follows:
[0073] (1) Take 10 μL of 10 μg / mL MC-LR and add it into 6 groups of 381 μL of 50 mM phosphate buffer solution (pH=7) in EP tubes, and mark the samples as 1, 2, 3, 4, 5, and 6 respectively.
[0074] (2) Take 5 μL of MlrA@DMOF with a concentration of 0.5 mg / mL and add it to samples 1, 2, 3, 4, 5, and 6 on days 0, 2, 4, 6, 8, and 10, respectively. After reacting at 25°C for 5 minutes, add 4 μL of 20% phosphoric acid aqueous solution to terminate the reaction. After centrifugation at 12000 rpm for 1 hour, the residual MC-LR in the supernatant was detected by HPLC.
[0075] (3) MlrA activity test control The same steps as above (1) and (2) were followed, except that MlrA was used instead of MlrA@DMOF.
[0076] The results are shown in Table 4
[0077] Table 3 Residual activity of MlrA@DMOF and MlrA at different storage times
[0078]
[0079] As can be seen from Table 4, MlrA completely lost its activity after 6 days of storage; however, MlrA@DMOF lost less activity over time, still retaining 68.3% of its activity on the 6th day and even 49.0% of its activity on the 10th day. Therefore, MlrA@DMOF can be stored for a longer time, which is beneficial for industrial applications.
[0080] Example 6
[0081] This example verifies the inhibitory effect of DMOF and MlrA@DMOF on Microcystis aeruginosa FACHB-905. The steps are as follows:
[0082] Microcystis aeruginosa FACHB-905 was cultured to the logarithmic growth phase and treated with DMOF, MlrA, MlrA@DMOF, and a mixture of DMOF and MlrA, respectively. Samples were taken on days 0, 1, and 2 to detect the cell number and pH value of the algal cells, and the inhibition rate was calculated by the cell number. The results are shown in Table 5. Table 4 Changes in cell number and pH of Microcystis aeruginosa treated with DMOF, MlrA, MlrA@DMOF, and a mixture of DMOF and MlrA on days 0, 1, and 2
[0083]
[0084] Figure 4 This is a diagram of the inhibitory effect of MlrA@DMOF on Microcystis aeruginosa FACHB-905. It can be seen from the figure that the algae solution in the MlrA@DMOF treatment group turned yellow, producing a significant algae inhibition effect, and the effect was better than the mixed solution of DMOF and MlrA and the single DMOF or MlrA treatment group, which is consistent with the measured cell number results.
[0085] In summary, a novel nanomaterial (DMOF) and its immobilized enzyme MlrA@DMOF and application in the embodiment of the present application have the following advantages: the present application produces a spherical mesoporous structure of DMOF by changing the order of addition of reactants in the system, and synthesizes MlrA@DMOF by biomimetic mineralization, which is simple to operate, low in price and high in efficiency. The mesoporous structure of DMOF is conducive to the contact between the substrate and the enzyme, prompting the enzyme to perform efficient catalytic reaction, and can protect the enzyme from the influence of high temperature, acid-base solution and other environments, and increase the circulation capacity and storage capacity of the enzyme. More importantly, the DMOF composite material allows large-sized substrates to enter the shell of DMOF, so this method is suitable for most enzymes.
[0086] This application obtains the immobilized enzyme MlrA@DMOF of DMOF by biomimetic mineralization method. Compared with similar non-porous MOF and typical similar material ZIF-8, the specific activity of the immobilized enzyme is more than doubled. After the DMOF is immobilized with MlrA, it has the effect of synergistically inhibiting the toxin-producing Microcystis aeruginosa FACHB 905, and has excellent catalytic ability, reaction stability, circulation ability and storage capacity, thus greatly broadening the application scope of the strategy of immobilizing enzymes on metal organic frameworks.
[0087] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present application.
Claims
1. A new type of nanomaterial, characterized in that: The nanomaterial is a spherical mesoporous material with a particle size of 2 to 30 μm and a surface pore size of 2 to 30 nm; The nano material is prepared by the following method: adding an alkali solution to a metal salt solution and fully mixing the mixture, then adding a ligand aqueous solution, and separating a solid product after sufficient reaction to obtain the nano material.
2. The novel nanomaterial according to claim 1, characterized in that: The concentration of the alkaline solution is 0.25-0.75% (w / w); the concentration of the metal salt aqueous solution is 20-400 mM, and the metal salt solution is a zinc salt, a copper salt, a cobalt salt or a nickel salt solution.
3. The novel nanomaterial according to claim 2, characterized in that: The zinc salt is at least one of nitrate, acetate, chloride and sulfate.
4. The novel nanomaterial according to claim 1, characterized in that: The ligand is one of 3-methyl-1,2,4-triazole and its derivatives, and the concentration of the ligand aqueous solution is 60-1200 mM.
5. The novel nanomaterial according to claim 1, characterized in that: The solid product is separated by centrifugation, specifically centrifugation at a speed of 6000-12000 rpm for 2-10 minutes.
6. An immobilized enzyme of the novel nanomaterial according to any one of claims 1 to 5, characterized in that: The particle size of the immobilized enzyme is 2-20 μm, and the pore size on the surface is 1-15 nm.
7. The immobilized enzyme of the novel nanomaterial according to claim 6, characterized in that: The immobilized enzyme is prepared by the following method: mixing an enzyme solution with a ligand aqueous solution, and then adding the mixture to a metal salt solution, wherein the final concentration of the enzyme in the mixture is 0.5 mg / mL, and separating a solid product to obtain the immobilized enzyme.
8. The immobilized enzyme of the novel nanomaterial according to claim 7, characterized in that: The enzyme solution is one or more of horseradish peroxidase, lysozyme, algae toxin degrading enzyme A, and algae toxin degrading enzyme C.
9. Use of the novel nanomaterial according to any one of claims 1 to 5 in inhibiting the growth of cyanobacteria and / or degrading algal toxins, characterized in that: The cyanobacteria is selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc, and Pseudo-Anabaena; and the algal toxin is selected from at least one of MC-LR, MC-YR, MC-RR, and Nodularin.
10. Use of the immobilized enzyme according to any one of claims 6 to 8 in inhibiting the growth of cyanobacteria and / or degrading algal toxins, characterized in that: The cyanobacteria are selected from at least one of Microcystis aeruginosa, Oscillatoria, Nostoc and Pseudo-Anabaena; and the algal toxins are selected from at least one of MC-LR, MC-YR, MC-RR and Nodularin.
Citation Information
Cited By
Novel algae-killing and detoxifying nano composite material as well as preparation method and application thereof
CN120683090A
Algaecidal detoxifying nanocomposite, and preparation method and application thereof
CN120683090B